2019
DOI: 10.1016/j.phytochem.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic variability of four macroalgal species of the genus Lobophora using diverse approaches

Abstract: Among comparative metabolomic studies used in marine sciences, only few of them are dedicated to macroalgae despite their ecological importance in marine ecosystems. Therefore, experimental data are needed to assess the scopes and limitations of different metabolomic techniques applied to macroalgal models. Species of the genus Lobophora belong to marine brown algae (Family: Dictyotaceae) and are widely distributed, especially in tropical coral reefs. The species richness of this genus has only been unveiled r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…For marine organisms, and especially non-model organisms, metabolite annotation is often limited by a lack of standards (e.g. Gaubert et al, 2019b, 2019a, Greff et al, 2017b, 2017aSogin et al, 2016). This issue is one of the greatest challenges in untargeted metabolomic studies (Kumar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For marine organisms, and especially non-model organisms, metabolite annotation is often limited by a lack of standards (e.g. Gaubert et al, 2019b, 2019a, Greff et al, 2017b, 2017aSogin et al, 2016). This issue is one of the greatest challenges in untargeted metabolomic studies (Kumar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The populations of L. rosacea growing at this site are assumed to have been exposed to acidified levels over the long-term (probably even for several generations). Because no L. rosacea was found in the other prospected mangrove areas presenting a normal pH, the site of Ricaudy (well studied for this species (Gaubert et al, 2019b(Gaubert et al, , 2019a was selected as our control site. It is a fringing coral reef flat where the seawater pH T is 7.99 ± 0.03 (pH T = pH in total scale), which is considered as within the normal pH range for shallow coastal reef flats in New Caledonia.…”
Section: Study Sites and Sampling For The In Situ Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The terpenoids isolated from the Dictyotaceae exhibit various types of bioactivity, such as feeding deterrence, anti-fungal, cytotoxic, antibiotic, anti-inflammatory, insecticidal or anti-viral activities (Vieira et al 2017). However, in the study by Gaubert et al (2019), no terpene derivatives were identified in the metabolome of the four species of Lobophora studied from New Caledonia. This observation could lead to interesting chemo-taxonomic considerations for this group and the search for terpene synthases in a larger set of Dictyotales.…”
Section: Secondary Metabolitesmentioning
confidence: 98%